Liability of Directors for Failure to Record Changes in Ownership of Inherited Shares - Farisi, Gusti Muhammad Reyhan; Alamsyah, Ariij Salsabil; Hardiansyah, Farid Naufal (Media Iuris, 2025)
Shares are a form of ownership of a person who has voting rights, rights to dividends, and rights to a share of assets in the event of liquidation. In the event that the owner of the shares dies, the transfer of ownership of the shares cannot occur immediately, but must go through a procedure so that the deed of rights to the shares is renamed to belong to the heirs. Cassation decision Number 2845 K/Pdt/2017 has set a new precedent; it was stated that the failure to record the heirs in the change of DPS was the negligence of the Board of Directors. So this research analyzes whether the Board of Directors is legally liable for the non-registration of heirs in the change of ownership of inherited shares, especially through systematic interpretation of article 50 paragraph (3) of the PT Law. This article is a legal research that uses primary and secondary legal sources in analyzing legal issues. The results show that the Board of Directors is passively obliged in terms of changes in ownership of shares in the DPS. So that the new obligation arises if the deed of change has been submitted to the company.